A Multidisciplinary approach to metastatic giant basal cell carcinoma: A case report - Lehto, Leo E. T. (Elsevier, 2025)
We present a case of a 49-year-old man with a giant basal cell carcinoma of the back, with metastases in the lungs, liver, mediastinum and both adrenal glands. Neoadjuvant vismodegib was administered, after which wide local resection of the tumour was performed. There have been no signs of local recurrence.